2018
DOI: 10.1128/aac.01246-17
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of FKS Hot Spot 1 from Saprochaete capitata To Search for a Relationship to Reduced Echinocandin Susceptibility

Abstract: , formerly known as , is an emerging fungal pathogen with low susceptibility to echinocandins. Here, we report the nucleotide sequence of the hot spot 1 region of the gene ( HS1), which codifies for the catalytic subunit of β-1,3-d-glucan synthase, the target of echinocandins. For that purpose, we first designed degenerated oligonucleotide primers derived from conserved flanking regions of the HS1 segment of 12 different fungal species. Interestingly, analysis of the translated HS1 sequences of 12 isolates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…S1). MICs of azoles were comparable to data from previous studies ( 6 , 8 , 9 , 28 , 29 ), and MICs of anidulafungin and caspofungin were high, as anticipated ( 9 , 30 ). In contrast, MICs of micafungin were lower, with M. clavatus isolates having significantly lower MICs (MIC 50 , 0.5 mg/L) compared to M. capitatus (MIC 50 , 2 mg/L; P < 0.001).…”
Section: Discussionsupporting
confidence: 87%
“…S1). MICs of azoles were comparable to data from previous studies ( 6 , 8 , 9 , 28 , 29 ), and MICs of anidulafungin and caspofungin were high, as anticipated ( 9 , 30 ). In contrast, MICs of micafungin were lower, with M. clavatus isolates having significantly lower MICs (MIC 50 , 0.5 mg/L) compared to M. capitatus (MIC 50 , 2 mg/L; P < 0.001).…”
Section: Discussionsupporting
confidence: 87%
“…In our observation, triazoles (except for fluconazole) showed potent in vitro activity against Saprochaete capitata with low MIC values. This is in agreement with data reported in the literature, which found that itraconazole, voriconazole and posaconazole (MIC ranges, 0.12 to 0.5, 0.25 to 0.5, and 0.03 to 0.5 µg/mL, respectively) have low MICs against Saprochaete capitata, but not fluconazole [17,36,46].…”
Section: Discussionsupporting
confidence: 93%
“…Clinical breakpoints for Saprochaete capitata are not available; however, antifungal susceptibility assays are recommended on all isolates [45]. Saprochaete capitata is considered intrinsically resistant to echinocandins; in particular, it was recently found that an F-to-L amino acid substitution in a highly conserved position of the catalytic subunit of β-1,3-dglucan synthase, Fks1p, might be related to a reduced susceptibility to echinocandins [46].…”
Section: Discussionmentioning
confidence: 99%
“…Based on in vitro susceptibility results from numerous case reports and case series, these organisms appear to be intrinsically resistant to echinocandins and highly resistant to fluconazole [3,11]. A mutation in the FKS gene hot spot 1 (FKS HS1) which codes a subunit in the β-1,3-D -glucan synthase was detected at a position highly associated with echinocandin resistance in S. capitata isolates [68]. Prolonged treatment with echinocandins (particularly caspofungin) appears to be a risk factor for breakthrough infections with these organisms [32,68], although breakthrough IFIs while on fluconazole, posaconazole and amphotericin B have also been reported [17,38,45,48,49,52].…”
Section: Antifungal Susceptibility and Treatmentmentioning
confidence: 99%
“…A mutation in the FKS gene hot spot 1 (FKS HS1) which codes a subunit in the β-1,3-D -glucan synthase was detected at a position highly associated with echinocandin resistance in S. capitata isolates [68]. Prolonged treatment with echinocandins (particularly caspofungin) appears to be a risk factor for breakthrough infections with these organisms [32,68], although breakthrough IFIs while on fluconazole, posaconazole and amphotericin B have also been reported [17,38,45,48,49,52]. Minimum inhibitory concentration (MIC) values for voriconazole (0.03-1 mg/L), amphotericin B (0.03-2 mg/L), itraconazole (0.01-1 mg/L) and posaconazole (0.03-1 mg/L) are generally low for both fungi [7,11,29,34,36,44,45,47].…”
Section: Antifungal Susceptibility and Treatmentmentioning
confidence: 99%